STAGES OF DEVELOPMENT OF THE PUBLIC ADMINISTRATION SYSTEM IN UZBEKISTAN DURING THE PERIOD OF INDEPENDENCE (1991–2016) - Abdullayev Mansur Masharibovich (Western European Studies, 2026)
This article analyzes the stages of formation and development of the public administration system in the Republic of Uzbekistan during the years of independence, in particular, in the period 1991–2016, based on a scientific-theoretical and historical approach. The study covers the issues of institutional reforms implemented in the field of public administration, the creation of legal frameworks, the improvement of the executive system, and the division of powers between central and local government bodies. The results of the article show that the public administration model of Uzbekistan has evolved and has gradually improved in accordance with national interests
Keywords: public administration; independence; political reforms